2016
DOI: 10.1039/c5ee03255e
|View full text |Cite
|
Sign up to set email alerts
|

Entropic stabilization of mixed A-cation ABX3 metal halide perovskites for high performance perovskite solar cells

Abstract: A mixture of CsPbI3 and FAPbI3 is thermodynamically stabilized in the perovskite phase with respect to the pure δ phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
1,085
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,174 publications
(1,131 citation statements)
references
References 33 publications
41
1,085
1
4
Order By: Relevance
“…The energy levels of the HOMO, band gap and the carrier mobility of electron transporting layer could be controlled by combination of hydrogen doping of I, Cl and Br with molar ratio in the perovskite crystal structure [18][19][20][21][22][23][24][25][26][27]. Incorporation of Cl and Br as dopants into the perovskite crystalline structure improved the crystal growth and size, the carrier transporting properties and the photovoltaic performance of Voc, Jsc and PCE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy levels of the HOMO, band gap and the carrier mobility of electron transporting layer could be controlled by combination of hydrogen doping of I, Cl and Br with molar ratio in the perovskite crystal structure [18][19][20][21][22][23][24][25][26][27]. Incorporation of Cl and Br as dopants into the perovskite crystalline structure improved the crystal growth and size, the carrier transporting properties and the photovoltaic performance of Voc, Jsc and PCE.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of both Cl and Br into the perovskite structure promoted the carriergeneration, and expanded carrier diffusion and lifetime, along with reducing the charge recombination in the active layers for improving the photovoltaic performance [14][15][16][17][18][19][20]. A detailed description of the photovoltaic properties, structural analysis, and theoretical investigation using Xray diffraction pattern (XRD), X-ray photoelectron spectroscopy, scanning electronic microscopy (SEM) and density-functional theory calculation of halogen-doped perovskite layer of CH3NH3PbI3−xClx, CH3NH3PbBr3−xClx, CH3NH3SnX3 (X = Cl, Br, I), [HC(NH2)2]0.83Cs0.17Pb(I0.6Br0.4)3], antimony-doped CH3NH3PbI3, CH3NH3Pb1−xGexI3, CH3NH3Pb1−xTlxI3 and CH3NH3Pb1−xInxI3 on TiO2 layers has been reported [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This is both thermal and moisture stability, and importantly stability to operation in the presence of oxygen. [60,61] Clearly, the next step forward is to optimize the solar cells with a more stable hole-transporter doping composition, which is a subject of ongoing study.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…3,37,38 Experimentally, it has been demonstrated that mixing a small amount of inorganic cations such as Cs + with methylammonium (CH 3 NH 3 + , i.e., MA + )/formamidinium (CH 3 (NH 2 ) 2 + , i.e., FA + ) at the A site significantly increases the stabilities of perovskite films. 2,[39][40][41] Contrast to the organicinorganic hybrid perovskites, purely inorganic CsPbX VII 3 perovskites exhibit excellent thermal stability. 3,38 Secondly, because the upper group-IVA elements such as Sn and Ge at the M IV site tend to be oxidized from divalent Sn 2+ /Ge 2+ to tetravalent Sn 4+ /Ge 4+ , 32,[42][43][44] and thus cause the instability issue, current halide perovskite based solar cells with high PCEs exclusively contain the toxic element -Pb.…”
Section: Introductionmentioning
confidence: 99%